2016
DOI: 10.3892/mmr.2016.5997
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles and networks in CXCL12-stimulated human endometrial stromal cells

Abstract: The chemokine stromal cell-derived factor-1 (C-X-C motif chemokine ligand 12; CXCL12) is important in the recruitment of leukocytes to the peritoneal cavity and the regulation of endometriotic tissue growth in endometriosis patients. However, the alterations in microRNA (miRNA) expression induced by CXCL12 remain to be fully elucidated. The present study evaluated key miRNAs in CXCL12-stimulated endometrial stromal cells (ESCs), and investigated the underlying cellular regulatory mechanisms of CXCL12 in endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This genomic region is associated with several solid tumors, such as prostate cancer [42], hepatocellular carcinoma [43] and breast cancer [44]. Previous studies showed that SH3BGRL2 was downregulated in esophageal squamous cell carcinoma [14], anaplastic thyroid carcinoma [45], ovarian chemotherapy resistance cells [15] and endometrial stromal cells [46]. Our study also found SH3BGRL2 was downexpression in ccRCC tumor than adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 75%
“…This genomic region is associated with several solid tumors, such as prostate cancer [42], hepatocellular carcinoma [43] and breast cancer [44]. Previous studies showed that SH3BGRL2 was downregulated in esophageal squamous cell carcinoma [14], anaplastic thyroid carcinoma [45], ovarian chemotherapy resistance cells [15] and endometrial stromal cells [46]. Our study also found SH3BGRL2 was downexpression in ccRCC tumor than adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 75%
“…Proteins, not genes, bestow cellular function, and therefore ESC cyst seem to have a more immunostimulatory phenotype than ESC endo [ 37 ]. CXCL12 is a ligand of the C-X-C chemokine receptor type (CXCR) 4, and through it, ESC cyst may further increase levels of inflammation in the pelvic cavity by recruiting CXCR4-positive immune cells [ 38 ]. Interestingly, ESC endo express CXCR4 and may hence be recruited to ectopic lesions by CXCL12, which may also possess nonimmune functions in endometriosis, such as promotion of tissue repair, angiogenesis, migration, invasion, and suppression of apoptosis [ 1 , 38 , 39 ], processes proposed to be involved in growth of ectopic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4/CXCL12 pathway and related molecular mechanisms have important roles to play in biological aggressiveness in metastasis and have therapeutic target for epithelial ovarian carcinoma (Jiang et al, 2006;Oda et al, 2007;Sekiya et al, 2012;. Certain studies have investigated the role of miRNA expression regulation and interaction with chemokine family as CXCR4/CXCL12 in healthy and cancer cells (Rhodes et al, 2011;Shen et al, 2014;Mei et al, 2017). These studies suggest that CXCR4/CXCL12 signaling stimulated tumorigenesis via microRNA regulation.…”
Section: Discussionmentioning
confidence: 99%